Coping with unpleasant surprises in a complex world: Is rational choice possible in a world with positive information costs? - Roger D. Congleton (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2011)
This paper provides a rational choice-based analysis of the causes and consequences of surprise events. The paper argues that ignorance may be rational, but nonetheless produce systematic mistakes, inconsistent behavior, and both pleasant and unpleasant surprises. If ignorance and unpleasant surprises are commonplace and relevant for individual and group decisionmaking, we should observe standing institutions for dealing with them - and we do. Insofar as surprises are consistent with rational choice models, but left outside most models, it can be argued that these methodological choices mistakenly limit the scope of rational choicebased research.
Keywords: D8; D6; 330; Ignorance; Rational Ignorance; Natural Ignorance; Bounded Rationality; Rational Choice; Biased Expectations; Crisis Management; Social Insurance; Bailouts; Economics of Information